Chylous Fistula Following Mastectomy - Faisal, Mohammad Israt (Journal of Enam Medical College, 2021)
Though chyle leakage after axillary dissection is a rare occurrence, sometimes it becomes difficult to manage. All surgeons dealing with breast should be aware with this unusual complication and its management. J Enam Med Col 2021; 11(2): 133-134